Designing and analyzing language tests - Carr, Nathan T (Oxford University, 2011)
Part I. Introduction -- 1. What are we testing and why? -- 2. Tasks - the building blocks of tests -- 3. Planning and designing the test -- 4. Writing the specifications for individual test tasks -- 5. Writing the test -- 6. Consistency of measurement -- 7. Rating scales for extended production tasks -- 8. Validation -- 9. Test administration -- 10. Other important topics in testing -- Part II. Introduction -- 11. Organizing data in microsoft excel -- 12. Descriptive statistics and standard scores -- 13. Creating graphs or charts in excel -- 14. Correlation -- 15. Item analysis for norm-referenced testing -- 16. Item analysis for criterion-referenced testing -- 17. Distractor analysis and scoring multiple-choice items in excel -- 18. Reliability : scoring consistency for norm-referenced tests -- 19. Dependability : scoring or classification consistency for criterion-referenced tests.; Includes bibliographical references and index